Transforming Islamic Da’wah Institutions for Achieving SDG 4 and SDG 16: A Strategic Management Perspective - Meity Suryandari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This conceptual paper explores the strategic transformation of Islamic Da’wah institutions to support the achievement of Sustainable Development Goals (SDG) 4 and 16. Drawing from strategic management theories and Islamic ethical frameworks, particularly maqashid shariah, the study proposes a model for institutional reform that aligns religious values with global development agendas. Through a literature-based analysis, the paper synthesizes key concepts such as visionary leadership, ethical governance, and inclusive education. The findings suggest that integrating Islamic principles into strategic planning enhances institutional accountability and educational quality. This study contributes to the discourse on Islamic institutional development by offering a conceptual framework that bridges faith-based governance with sustainable development.